"I try to pray and i think of something clever": Katherine Mansfield and modernist prayer - Cappuccio, Richard (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Katherine Mansfield was raised in a culture that instilled prayer as central to daily life. She recorded her first extant diary entry in her "Book of Common Prayer"; those penciled notes started a lifelong dialogue with religion. However, Mansfield`s emphasis on individuality and art over tradition resulted in her ambivalence towards religion; she was critical of a piety learned by rote and of a dogma to which one blindly adhered.
Keywords: prayer; modernism; the penitent in literature; modernist reactions to religion; Mansfield, Katherine (pseud.); Mansfield Murry, Kathleen (1888-1923); Eliot, Thomas Stearns (1888-1965)